Model Strategis Internalisasi Nilai dan Ajaran Agama pada Peserta Didik di Lingkungan Madrasah - Binti Nasukah; Rita Anina Fidayanti (LP2M Universitas Ibrahimy, 2024)
Madrasas have now developed into the community's choice. The negative influence of the environment due to globalization and the development of information technology is the reason why parents choose madrasas. There is hope that madrasas as a type of Islamic educational institution can educate their children to have noble character and morals, who apply Islamic religious values in everyday life. This is the background to the importance of studying how madrasas are able to meet the expectations of their constituent communities. For this reason, the research aims to find out how strategies for internalizing religious values and teachings to students are implemented by madrasas, taking the location at Madrasah Tsanawiyah Negeri (MTsN) 5, Malang (Regency). The method used is qualitative with a case study approach. Primary data collection used interview techniques with madrasa heads, teachers & students; and observation techniques in the school environment and various religious activities carried out. The research results show that there are three strategic steps that educational institutions need to take to be successful in internalizing students' religious values and teachings: 1) Establishing a policy on religious values and programs that serve as guidelines for joint implementation; 2) Implementing values and programs through habituation and example; 3) Providing reinforcement through providing advice and disciplinary supervision. The results of this research contribute a theoretical and practical guide for academics and educational management practitioners that in an effort to internalize a particular value or teaching, a step-by-step process is needed which starts with policy making, then implemented, and then given reinforcement to achieve the goal of establishing character can succeed.